Effects of whole-body vibration training on physical function, activities of daily living, and quality of life in patients with stroke: a systematic review and meta-analysis - Zeng, Duchun; Zhao, Kun; Lei, Wei; Yu, Yanmei; Li, Weili; Kong, Yurou; Lai, Junmei; Ma, Fenghao; Ye, Xiangming; Zhang, Xiaofeng (Frontiers in Physiology, 2024)
Purpose: This systematic review and meta-analysis aimed to evaluate the efficacy of whole-body vibration training (WBVT) in patients with stroke, specifically focusing on its effects on physical function, activities of daily living (ADL), and quality of life (QOL). Additionally, potential moderators influencing WBVT outcomes were explored. Methods: We conducted a systematic search of PubMed, Embase, and Cochrane Library from inception to September 2022. Eligible studies were randomized controlled trials employing WBVT in patients with stroke. Two investigators independently extracted the data and calculated the standardized mean difference (SMD) using random-effect models. Results: Twenty-five studies involving 991 patients were included in this meta-analysis. WBVT demonstrated significant reductions in spasticity (SMD = −0.33, 95% CI = −0.61 to −0.06, P = 0.02), improvements in motor function (SMD = 0.39, 95% CI = 0.16 to 0.61, P < 0.01), and enhancements in balance function (SMD = 0.28, 95% CI = 0.09 to 0.47, P < 0.01) in patients with stroke. However, no significant effects were observed for gait (SMD = −0.23, 95% CI = −0.50 to 0.04, P = 0.10), ADL (SMD = −0.01, 95% CI = −0.46 to 0.44, P = 0.97), or QOL (SMD = 0.12, 95% CI = −0.30 to 0.53, P = 0.59). Subgroup analyses revealed that variable frequency vibration and side-alternating vibration exhibited significant efficacy in reducing spasticity and improving motor and balance functions, while fixed frequency vibration and vertical vibration did not yield significant therapeutic benefits in these domains. Conclusion: Our findings indicate that WBVT may serve as a viable adjunct therapy for stroke patients to alleviate spasticity and enhance motor and balance functions. Variable frequency and side-alternating vibration appear to be crucial factors influencing the therapeutic effects of WBVT on these dysfunctions. Nonetheless, WBVT did not show significant effects on gait, ADL, or QOL in stroke patients.